Uptake of e-Scooters in Palermo, Italy: Do the Road Users Tend to Rent, Buy or Share? - Campisi, Tiziana; Akgün Tanbay, Nurten; Md Nahiduzzaman, Kh.; Dissanayake, Dilum (Springer Science and Business Media Deutschland GmbH, 2021)
The uptake of micro-mobility, particularly the use of e-scooters has exponentially grown in Europe. The EU strategies have led to promote the decisions of purchasing, renting and/or sharing e-scooters by making some vital changes to the infrastructure. Several companies have made it possible to rent or share vehicles, while many manufacturers have marketed different models. During the COVID-19 pandemic, e-scooters have become widely popular for short distance travel in Italy as they allow the potential to maintain a social distancing. This paper aims to explore the uptake of e-scooters with an attention to propensity to buy, rent or share those sustainable urban mobility alternatives as well as user perceptions and frequency of use by comparing the periods before and during the third phase of the pandemic. Two sets of surveys were carried out with 200 participants who habitually use e-scooters in Palermo, Italy. 77.5% of the participants had to commute to work during the third phase of the pandemic. Majority of the participants preferred e-scooters as they were economic and environmentally friendly. Road users tended to buy or rent e-scooters during the third phase of the pandemic but they hesitated to share. The results of this study will enhance our understanding of the demand for micro-mobility in the context of interest and will allow for a better planning in consideration to the available options to purchase, share and rent.
Keywords: COVID-19; E-scooters; Renting; Shared mobility; Sustainable transport